Analisis Efisiensi Baitul Maal Wa Tamwil (BMT) Dengan Pendekatan Data Envelopment Analysis (Studi BMT Di Kota Jambi) - Maulana Hamzah, Muhammad (DPPM Universitas Pelita Bangsa, 2024)
The development of BMTs in Jambi is rapidly increasing, data from BPS shows the number of BMTs in Jambi City amounted to 21 in 2018 and increases every year. However, these developments have not been matched by improving the quality of management and financial efficiency, it is necessary to map out evaluations related to the effectiveness and efficiency of the BMT. This study aims to analyze the level of efficiency and effectiveness with DEA (Data Envelopment Analysis) method. The sample in this study used the convenient sampling method, namely the sample was selected based on the willingness of the BMT management to be part of the study. The secondary data used is sourced from the financial statements of each BMT. The input variables are third party funds (X1), personnel costs (X2) and general/administrative expenses (X3). While the output is the amount of financing disbursed (Y1), operating profit income (Y2) and other operating income (Y3). The research results found that of the 13 BMTs observed, only 5 BMTs were active, but only 4 of them had consistent financial reports. Of the 4 BMTs, only 3 BMTs were willing to provide financial report data. The results found that all BMTs operated efficiently in 2022, but BIS experienced inefficiency in 2020 (92.76%) and 2021 (92%). BMT ISH experienced inefficiency in 2021 with a value of 71.5%. The point of BMT's inefficiency in that year was dominated by the burden of managing TPF, operational costs, and less than optimal income from other businesses.